Deriving Other Algebras from AOP
Back Home Main Next  

Home News Links Search Feedback Software Elements
Researches AOP Degeneracy GTODE Implementations Optimum Download

AOP

Paper-1
TOC-1

Tables
Figures
Computer
Symbols
Researches

Degeneracy

Paper-1
Paper-2
Paper-3
Paper-4
Researches

GTODE

Paper-1
Paper-2
Paper-3
Paper-4
Researches

 

Contents Deriving Boolean, Deriving Post, Deriving Kleenean, Deriving Kleene's Laws
See also TOC
Abstract Introduction Priority Unary Prioritors Operations
TAS Theorems Orthogonal Expansion Image-Scaling Degeneracy
Design Derive  AOP Versus Tables Figures Proofs
Computer Bibliography        

Deriving Other Algebras From AOP

Deriving BOOLEAN ALGEBRA FROM AOP

Boolean algebra can be derived from AOP by: 

  1. Replacing the a prioritor by the AND and the a* prioritor by the OR operator or vise versa.

  2. Replacing any orthogonal or unary operator by NOT 

  3. Replacing any conservative unary operation by the NOT operator  

  4. Replacing 'z' by '2' in statistical theorems

Table-8: Derivation of Boolean Algebra
Theorem Case 1  
a
=·, a*=+, a#= ¾
Case 2  
a=+, a*=·, a#= ¾

Inferiority

1·A=A

0+A=A

Superiority

0·A=0

1+A=1

Distribution Theorem

A·(B+C)=(A·B)+(A·C)

A+(B·C)=(A+B)·(A+C)

Idempotence Theorem

A·A=A

A+A=A

Association Theorem

A·(B·C)=(A·B)·C

A+(B+C)=(A+B)+C

Commutation Theorem

A·B=B·A

A+B=B+A

Absorption Theorem-I

A·(A+B)=A

A+(A·B)=A

Exclusion Theorems

 ·( A+B)=A·B

A¯+( A ·B)=A+B

Static Theorem

 ·A=0

A ¯+A=1

Uniform Degeneracy

Dual ·=+

Dual +=·

 Image-Scaling

(A·B)¯= A¯ + B¯

(A+B)¯ = A¯ ·

 Expansion

f(X)=(X¯·f(0))+(X·f(1))

f(X)=(X¯+f(0))·(X +f(1))

Derivation of Post Algebra

          Post algebra as defined by Muzio p.93 in [8] can be derived from AOP by: 

  1. Replacing the a prioritor by the MIN and the a* prioritor by the MAX operator or vise versa. 

  2. Using MINL=0 and MAX L=z-1, MINÚ=z-1 and MAXÚ=

  3. Replacing Dm0(z-1) by Cm and Dm(z-1)0 by Jm, where Jm(X)={0 if X=m, z-1 otherwise} Cm(X)={z-1 if X=m, 0 otherwise} . 

  4. Replacing any conservative unary operation by the MV-NOT operator.  

  Derivation of Post Algebra

Theorem

 Case 1  
a=·, a*=+, a#= ¾

Case 2
a=+, a*=·, a#= ¾

Inferiority Theorem

(z-1)·A=A

0+A=A

Superiority Theorem

0·A=0

(z-1)+A=(z-1)

Distribution Theorem

A· (B+C)=(A·B)+(A·C)

A+(B·C)=(A+B)·(A+C)

Idempotence Theorem

A·A=A

A+A=A

Association Theorem

A·(B·C)=(A·B)·C

A+(B+C)=(A+B)+C

Commutation Theorem

A·B=B·A

A+B=B+A

Absorption Theorem-I

A·(A+B)=A

A+(A·B)=A

Image-Scaling Theorem

 (A·B)¯= A¯+ B¯

(A+B)¯= A¯· B¯

Uniform Degeneracy

Dual ·=+

Dual +=·

Exclusion Theorem

A·(C0(A)+B)=A·B

A+(Jz-1(A)·B)=A+B

Variable Expansion

      m=z-1
X=
S (m·Cm(X))
      m=0

      m=z-1
X=
P (m+Jm(X))
      m=0

Static Theorem

A·C0(A)=0

A+Jz-1(A)=z-1

The table listed below shows the derivations steps for the static, quasi-static, and variable expansion theorems. 

Static Theorem: In Case-1

Explanation


AaAD aL aL B = a L

Letting B=aÚ and using the ‘Cm(x)’ definition we replace the orthogonal operator by CaL(A)

AaCaL(A)=a¾  L

Letting a=· and using   ·L=0

A·C0(A)=0

Q.E.D.

Static Theorem: In Case-2

Explanation


AaAD aL aL B  = a L

Letting B=aÚ and using the ‘Jm(x)’ definition we replace the orthogonal operator by JaL(A)

AaJaL(A)=a¾L

Letting a=+ and using +¾  L=z-1

A+Jz-1(A)=z-1

Q.E.D.

Quasi Static Theorem Case-1

Explanation

Aa(AD aL aL B  a* B) = AaB

Letting C=aÚ and using the ‘Cm(x)’ definition we replace the sione orthogonal operator by CaL(A)

Aa( CaL(A) a* B) = AaB

Letting a=· and using ·¾  L=0;

A·(C0(A)+B)=A·B

Q.E.D.

Quasi Static Theorem Case-2

Explanation

Aa(AD aL aL Ba* B) = AaB

Letting C=a──Ú and using the ‘Jm(x)’ definition we replace the orthogonal operator by JaL(A)

Aa( JaL(A) a* B) = AaB

Letting a=+ and using +¾L=z-1 +*=·

A+ (Jz-1(A) ·B)=A+B

Q.E.D.

Variable Expansion : Case-1

Explanation

      a*: (z-1)
 X=P (m a  x¾   Dma¾ La Ú )
      m=0

From the expansion theorem-I (theorem-16). Letting a=· and using ·¾ L=0; ·Ú=(z-1); ·*=+ and using the ‘Cm(x)’ definition

     z-1
X=
S (m · Cm(x))
     m=0

Cm(x)= x¾   Dma¾ La Ú= x¾  Dm0(z-1)

Q.E.D.

Variable Expansion : Case-2

Explanation

     z-1  
X=
P (m+Jm(x))  
     m=0

Letting a=+ and using +¾L=z-1; +¾V=0; +*=· and using the Jm(x) definition and follow the steps in case-1.  

Q.E.D.


 

Deriving Kleenean Algebra As Defined By [12]

Table-5: Derivation of Kleenean Algebra from AOP

No  

Theorem Name under AOP

Case-1  
a
=·, a*=Ú, a#= ¾

Case-2  
 
a=Ú, a*=·, a#= ¾

1

Inferiority Theorem

1·A=A

0ÚA=A

2

Superiority Theorem

0·A=0

1ÚA=1

3

Distribution Theorem

A·(BÚC)=(A·B) Ú(A·C)

AÚ(B·C)=(AÚB)·(AÚC)

4

Idempotence Theorem

A·A=A

AÚA=A

5

Association Theorem

A·(B·C)=(A·B)·C

AÚ(BÚC)=(AÚB) ÚC

6

Commutation Theorem

A·B=B·A

AÚB=BÚA

7

Absorption Theorem-I

A·(AÚB)=A

AÚ(A·B)=A

8

Absorption Theorem-III

(A¯· A )·(B¯Ú B)=(A¯·A)

(A¯·A )Ú(B¯Ú B) =( B¯Ú B)

9

Costar Theorem

A==A

A==A

10

Uniform Degeneracy

Dual ·=Ú

Dual Ú=·

11

Image-Scaling Theorem

(A·B)¯= A¯ Ú

(AÚB)¯ = A¯ ·

 

Deriving the Kleene's Laws from the Absorption Theorem III

The Kleene's laws are: (1) (A·A¯)·(BÚB¯)= (A·A¯) and (2) (A·A¯)Ú (BÚB¯)= (BÚB¯). The '·' operator in this law represents the MIN operator and 'Ú' represents the MAX operator. The DnDel Ñ prioritor in AOP corresponds to the MAX operator and the UpDel prioritor D corresponds to the MIN operator.  

Kleene's laws are: (1) (A·A¯)·(BÚB¯)= (A·A¯) and (2) (A·A¯)Ú (BÚB¯)= (BÚB¯). The '·' operator in this law represents the MIN operator and 'Ú' represents the MAX operator. The DnDel prioritor “Ñin AOP corresponds to the MAX operator and the UpDel prioritor “D” corresponds to the MIN operator.

Deriving the First Law

 

(AaA¾  a#)a(Ba*B¾  a#)=(AaA¾  a#)

Absorption theorem-III

(A·A¾ · #)·(B·*B¾ · #)=(A·A¾ · #)

Letting a=·

(A·A¾ · #)·(BÚB¾ · #)=(A·A¾ · #)

Since ·=D, then ·*=D*=Ñ=Ú

(A·A¾  D)·(BÚB¾  D)=(A·A¾  D)

Since ·=D, then 
·#=D#=D-¾D*=D¾Ñ =D

(A· A¯ )·(BÚ B¯)=(A·A¯)

Since the bar '¯' in Boolean, Post and Kleenean algebras corresponds to D operator in AOP. Q.E.D.

Deriving the Second Law

 

(AaA¾  a¾  )a(Ba*B¾  a#)=(AaA¾  a#)

Absorption theorem-III

(AÚA¾Ú  #)Ú (BÚ*B¾Ú  #)=(AÚA¾Ú  #)

Letting a=Ú

(AÚA¾Ú  #)Ú (B·B¾Ú  #)=(AÚA¾Ú  #)

Since Ú=Ñ, then Ú*=Ñ*=D=·

(AÚA¾  D)Ú (B·B¾  D)=(AÚA¾  D)

Since Ú=D, then Ú#=Ñ#=
Ñ-¾Ñ *=Ѿ D=D

(AÚ A¯)Ú (B· B¯ )=(AÚ A¯ )

Since the bar '¯' in Boolean, Post and Kleenean algebras corresponds to D operator in AOP.

(B· B¯ )Ú(AÚ A¯) =(AÚ A¯ )

Since Ú is a commutative operator we re-order the terms on the left side

(A· A¯ )Ú(BÚ B¯) =( BÚ B¯)

By letting A=B and B=A which does not change the equation. This is Kleene's second law. Q.E.D.

 

  

Back Home Main Next

Webmaster tech@50megs.com with questions or comments about this web site.
General Information: abumsamh@emirates.net.ae
Copyright © 2000 GTODE on Internet
Designed by: R. K. Abu-Msameh
Last modified: February 18, 2001

IEEE International Symposium MVL

Logic Technical Committee

MVL  International Journal.